Hypotensive Effect of Heated Water-based Exercise in Older Individuals with Hypertension - Ngomane, Awassi Yophiwa [UNESP]; Fernandes, Bianca [UNESP]; Guimarães, Guilherme Veiga; Ciolac, Emmanuel Gomes [UNESP] (Thieme, 2019)
Blood pressure (BP) and hemodynamic response to heated water-based (HEx) vs. land-based exercise (LEx) were assessed in 15 (6 men) older hypertensives (age 66.4±4.9 yr) under pharmacological treatment. Participants were randomly assigned to perform 30 min of moderate-intensity HEx (walking inside the pool), LEx (walking on a treadmill) and non-exercise control (CON) intervention. Resting BP, arterial stiffness, endothelial reactivity and heart rate variability (HRV) were measured before, immediately after, and 45 min after interventions. 24-h ambulatory BP monitoring was performed after interventions. Resting systolic (but not diastolic) BP reduced 9.9±3.1 mmHg (P <0.01) 45 min after HEx only. 24-h systolic and diastolic, daytime diastolic and nightime systolic BP were lower (P <0.05) after HEx than both LEx and CON. Daytime systolic BP was also lower (P <0.05) after HEx than CON. Nighttime diastolic was not different between interventions. HEx-induced ambulatory BP reduction ranged 4.5±1.3 mmHg (24-h diastolic BP) to 9.5±3.0 mmHg (nighttime systolic BP), and persisted for 18/11 h in systolic/diastolic BP, when compared with CON. No significant changes in arterial stiffness, endothelial reactivity and HRV were found during any intervention. These results suggest that HEx may have important implications for managing BP in older hypertensive under pharmacological treatment.
Keywords: aging; arterial stiffness; endothelial function; exercise; heart rate variability; hypertension